Resistance training before, during, and after COVID-19 infection - Gentil, Paulo (2022)
At the end of 2019, a severe acute respiratory syndrome caused by SARS-CoV-2 started a pandemic, leading to millions of deaths and many important political and social changes. Even in the absence of contamination, the mobility reduction, social distancing and closing of exercise facilities negatively affected physical activity and conditioning, which is associated with muscle atrophy, loss of muscle strength, and reductions in functional capacity. In cases of infection, it has been shown that increased physical capacity is associated with decreased hospitalization and mortality risk. Although millions of people have died from COVID-19, most contaminated individuals survived the infection, but carried different sequelae, such as the severe loss of physical function and a reduced quality of life. Among different physical exercise models that might help to prevent and treat COVID-19-related conditions, resistance training (RT) might be particularly relevant. Among its benefits, RT can be adapted to be performed in many different situations, even with limited space and equipment, and is easily adapted to an individual’s characteristics and health status. The current narrative review aims to provide insights into how RT can be used in different scenarios to counteract the negative effects of COVID-19. By doing this, the authors expect to provide insights to help deal with the current pandemic and similar events the world may face in the future.